PERAN UNITED NATIONS ENVIRONMENT PROGRAMME (UNEP) DALAM MENANGANI POLUSI MARINE PLASTIC DEBRIS DI LAUT ASIA TIMUR - Junida Siregar; Den Yealta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study is a contemporary study that provides an analysis of the role of UNEP in addressing marine plastic debris pollution in the East Asian Seas (EAS). This study aims to explain the causes and impacts of marine plastic debris pollution in the EAS. The excessive use of plastic and poor waste management systems are common factors causing marine plastic debris pollution in the EAS. These have caused a lot of damage and losses to the marine and coastal environment of the EAS. UNEP as the leading global environmental authority is concerned to address marine plastic debris pollution in the EAS.This research was developed based on the framework of pluralism perspective that is supported by the theory of international organization and environmentalism, as well as the level of analysis using international organization as the main actor in international relations. The concept leads to qualitative methods and the study of literature as a source of information.The roles of UNEP are as a catalyst, advocate, educator and facilitator. The roles of UNEP can be seen from the efforts it has made regionally and globally which have significant impacts in the East Asian Seas.Keywords: Marine Plastic Debris, Seas Pollution, Role, UNEP, East Asian Seas